2012
DOI: 10.1080/00268976.2012.700407
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous transport properties of hydrogen, deuterium and their binary mixtures fromab initiopotential

Abstract: A spherically symmetric representation of the ab initio potential, developed , J. Chem. Phys. 129, 094304 (2008) [16], has been used to calculate transport properties of hydrogen, deuterium and their binary mixtures by means of the classical kinetic theory. Results are reported for viscosity, thermal conductivity, diffusion coefficient and thermal diffusion factor in the dilute-gas limit for temperatures ranging from 298 to 2000 K. Available experimental data have been investigated and compared with the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Hurly and Moldover and Mehl et al reported the transport property values for helium and hydrogen, respectively, using a full quantum-mechanical formalism. The comparison of our previous work , with the theoretical values by Hurly and Moldover as well as Mehl et al shows that the difference is less than 0.7% for viscosity, 0.3% for thermal conductivity, and 0.9% for diffusion coefficient at room temperature.…”
Section: Theoretical Evaluation Of Transport Propertiessupporting
confidence: 63%
See 3 more Smart Citations
“…Hurly and Moldover and Mehl et al reported the transport property values for helium and hydrogen, respectively, using a full quantum-mechanical formalism. The comparison of our previous work , with the theoretical values by Hurly and Moldover as well as Mehl et al shows that the difference is less than 0.7% for viscosity, 0.3% for thermal conductivity, and 0.9% for diffusion coefficient at room temperature.…”
Section: Theoretical Evaluation Of Transport Propertiessupporting
confidence: 63%
“…We utilized the classical kinetic theory to compute transport properties, where the isotropic potentials of like and unlike interactions are necessary. The detailed information on the He 2 and (H 2 ) 2 potentials were given in our previous publications , so that they are not repeated here. For the He–H 2 system, the 2D potential function of ref can be simplified to a one-dimensional form by including only the terms with a variable subscript of 0, where V is the interaction energy as a function of the intermolecular distance R .…”
Section: Theoretical Evaluation Of Transport Propertiesmentioning
confidence: 99%
See 2 more Smart Citations